2010
DOI: 10.1021/ma100893s
|View full text |Cite
|
Sign up to set email alerts
|

Branched Poly(phenylacetylene)

Abstract: Characterization of poly(phenylacetylene) (PPA) samples produced using Rh(I) complexes featuring hemi-labile phosphine ligands by size exclusion chromatography, multi-angle light scattering, (SEC-MALS), or asymmetric field flow fractionation (A4F)-MALS has revealed that some of these PPA samples contain a mixture of linear and branched polymer. The occurrence and extent of branching is dependent on both catalyst structure and polymerization conditions. The levels of branching are consistent with either termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…S7 in Supporting Information). Jiménez and co‐workers have recently suggested the mechanism for terminating reaction of the PA polymerization with the formation of a phenylethynyl terminating end 53. Although further investigation is required for full characterization of the terminating end in our current case, it can be concluded that each polymer chain of all the produced poly(PA)s bears one R group at the initiating chain end.…”
Section: Resultsmentioning
confidence: 77%
“…S7 in Supporting Information). Jiménez and co‐workers have recently suggested the mechanism for terminating reaction of the PA polymerization with the formation of a phenylethynyl terminating end 53. Although further investigation is required for full characterization of the terminating end in our current case, it can be concluded that each polymer chain of all the produced poly(PA)s bears one R group at the initiating chain end.…”
Section: Resultsmentioning
confidence: 77%
“…We have shown that cationic rhodium(I) complexes [Rh (diene){Ph 2 P(CH 2 ) n Z}] + (n = 2 or 3; Z = OMe, NMe 2 ) efficiently catalyze PA polymerization leading to very high-molecularweight stereoregular PPAs with a cis-transoidal configuration and moderate dispersity. 12,13 Reactivity studies on the catalyst precursor [Rh(cod){Ph 2 P(CH 2 ) 3 NMe 2 }] + revealed that the -NMe 2 group behaves as an internal base for the PA deprotonation to afford the alkynyl species [Rh(CuC-Ph)(cod){Ph 2 P-(CH 2 ) 3 NHMe 2 }] + which actually is the initiating species likely involved in the generation of stable rhodium-vinyl species responsible for the propagation step. 12 Interestingly, characterization of the polymers by size exclusion chromatography, multiangle light scattering (SEC-MALS), or asymmetric flow field flow fractionation (A4F-MALS), showed that some PPA samples contained branched PPA of high molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…12 Interestingly, characterization of the polymers by size exclusion chromatography, multiangle light scattering (SEC-MALS), or asymmetric flow field flow fractionation (A4F-MALS), showed that some PPA samples contained branched PPA of high molecular weight. 13 The emergence of N-heterocyclic carbenes (NHCs) in the last two decades has spurred the development of organometallic catalysis gradually displacing the typical phosphine and amine-type ligands. Their strong σ-donor character results in very strong metal-NHC bonds, making the catalysts more robust.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, asymmetric‐flow field‐flow fractionation, AF4, has been used to avoid interactions between the polymer and the stationary phase. Although the macromolecules analyzed by AF4 are in contact with the semipermeable membrane of the accumulation wall, the total contact surface is much lower compared to the packed porous SEC columns and thus enthalpic interactions are less likely .…”
Section: Introductionmentioning
confidence: 99%